Research advances in hypertriglyceridemia-induced acute pancreatitis - Yongxia Cai; Xizhu Huang (Frontiers in Medicine, 2026)
Hypertriglyceridemia-induced acute pancreatitis (HTG-AP), a significant subtype of acute pancreatitis (AP), is witnessing a rising global incidence and is associated with a poorer clinical prognosis compared to AP of other etiologies. This review outlines the fundamental theories, clinical characteristics, diagnostic modalities, therapeutic strategies, and future research directions concerning HTG-AP, with a particular emphasis on recent advancements in molecular biology, precision medicine, and therapeutic technologies. Epidemiological data reveal that patients with HTG-AP exhibit significantly higher rates of severe disease (46.9%) and multiple organ dysfunction syndrome (MODS) compared to those with AP of other causes; furthermore, concomitant biliary diseases or alcohol consumption exacerbate disease severity. Current evidence indicates that the pathogenesis of HTG-AP involves multifaceted mechanisms, including oxidative stress, activation of inflammatory signaling pathways, and intestinal barrier dysfunction. Notably, the crosstalk between the JAK2/P38MAPK signaling pathway and oxidative stress represents a pivotal mechanism. In terms of diagnosis, metabolomics has identified specific biomarkers such as phosphatidylethanolamine (PE), demonstrating a diagnostic area under the curve (AUC) of up to 0.962. Regarding treatment, the combination of plasma exchange and hemofiltration can rapidly reduce triglyceride (TG) levels (by up to 69.57%); however, the trade-off between cost and efficacy warrants careful consideration. Future research should prioritize the development of innovative diagnostic tools, the optimization of personalized therapeutic strategies, and the construction of comprehensive prevention systems to enhance the overall management of HTG-AP.